Asymetria pomiędzy nauczaniem języka polskiego jako obcego na włoskich uniwersytetach a nauczaniem języka włoskiego jako obcego na polskich uniwersytetach - Rogalska-Chodecka, Katarzyna (Neofilolog, 2026)
The purpose of this article is to present an analysis of teaching Polish as a foreign language at Italian public universities and compare it with academic-level teaching of Italian in Poland. The unconventional impetus for this research arose from the challenges faced by Polish students of Italian Studies, or Applied Linguistics with Italian, in finding equivalent translation courses during their Erasmus+ exchange in Italy. The contexts differ significantly. Whereas holistic Italian Studies can be found at most major public universities in Poland, Polish Studies in Italy is narrower in scope and less popular. An observable recent trend indicates that access to study of Polish will be further restricted. Due to a decrease in student numbers Polish courses are not opened every year. In this article this phenomenon is examined, detailed lists of Polish universities offering Italian Studies and Italian universities offering Polish Studies are provided, with attention given to observable asymmetry and its causes. Ways of addressing the problem are suggested.